1997
DOI: 10.1016/s0002-9149(97)00707-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Accuracy of Dobutamine Stress Echocardiography for the Diagnosis of Coronary Artery Disease

Abstract: The accuracy of dobutamine stress echocardiography (DSE) for the diagnosis of coronary artery disease (CAD) has not been yet evaluated in women. We studied the effect of gender on the accuracy of DSE for the diagnosis of CAD in 306 consecutive patients (210 men and 96 women) with limited exercise capacity and suspected myocardial ischemia who underwent coronary angiography within 3 months of DSE. There were no serious complications during DSE. Men had a higher prevalence of nonsustained ventricular tachycardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…DSE had a higher sensitivity but a lower specificity than those of stress echocardiography performed with dipyridamole or adenosine. 75,76 Similar to the results for exercise stress echocardiography in women, the diagnostic accuracy of DSE to detect CAD in women appears to be similar to that in men.…”
Section: Diagnosissupporting
confidence: 62%
“…DSE had a higher sensitivity but a lower specificity than those of stress echocardiography performed with dipyridamole or adenosine. 75,76 Similar to the results for exercise stress echocardiography in women, the diagnostic accuracy of DSE to detect CAD in women appears to be similar to that in men.…”
Section: Diagnosissupporting
confidence: 62%
“…Diagnostic accuracy in the three coronary arterial distributions. Previous studies have demonstrated a modest sensitivity for DSE in diagnosing significant CAD in an individual coronary artery as well as in patients with singlevessel CAD (1)(2)(3)(4)(5)(6)(7). In this study, MCE had a significantly higher sensitivity and accuracy than WMA for the diagnosis of LAD, RCA, and LCx CAD.…”
Section: Discussionmentioning
confidence: 52%
“…However, pooled data have shown that the sensitivity of wall motion analysis (WMA) is modest, particularly in patients with single-vessel CAD (1)(2)(3)(4)(5)(6)(7). Although patients with multivessel CAD often demonstrate wall motion abnormalities during DSE, abnormalities are often detected in a single vascular region, with underestimation of the extent of CAD (1).…”
mentioning
confidence: 99%
“…108 The majority of dobutamine stress echocardiography studies in women have reported sensitivities ranging from 75% to 93% and specificities from 79% to 92%. [113][114][115][116][117] A meta-analysis of dobutamine stress echocardiography found an overall sensitivity of 80% (95% CI, 77%-83%) and specificity of 84% (95% CI, 80%-86%). 108 For exercise and dobutamine stress echocardiography, the diagnostic accuracy is generally comparable among women and men, although the prevalence of CAD by angiography is generally lower for women.…”
Section: Role Of Stress Echocardiography In Diagnosis and Risk Assessmentioning
confidence: 99%